ANALISIS PENDAPATAN, EFISIENSI DAN PEMASARAN SEMANGKA (CITRULLUS VULGARIS) DI KAMPUNG TEMPURAN KECAMATAN TRIMURJO KABUPATEN LAMPUNG TENGAH - Efrizal, Yozi; Nurung, M.; Mulyasari, Gita (Jurnal AGRISEP, 2011)
This study is aimed  at determining the revenue, efficiency and marketing of watermelon (Citrullus vulgaris) farming in Kampung Tempuran, Trimurjo District, Central Lampung District, Lampung Province with a total of 27 respondents who were selected by using census method. Revenue is obtained bydeducting the total income by  the total cost, efficiency is the ratio (ratio) between income and total cost. Watermelon marketing is analysed by identifying marketing channel from the producer to the end consumer  and by estimating the marketing margin of watermelon on each marketing channel. Marketing margin is estimated by subtracting the selling price with buying price. The results showed that the average farm income of at Rp.237.506.694/Ut/MT watermelon or watermelon farm efficiency Rp.34.852.801/Ha/MT. Revenue Cost Ratio is obtained 3.81meaning that  melon farming is  efficient or profitable.  There are three marketing channels.  Based on one of marketing channels studied, it is found that marketing margin of watermelon from farmers as  producers  to  wholesalers s is Rp. 784/Kg. From the wholesaler to the retailer, the marketing margin   is Rp. 1500, - / Kg.Keywords: farm income, efficiency, marketing channels, marketing margins.